Diamagnetophoresis for sorting of particles - Tiang, Zi Hua (2016)
Diamagnetophoresis has been gaining more attention in the recent years due to the benefits that it can bring to the field of micro-magnetofluidics. This process has great potential in the sorting of micron-sized particles. The main difference between diamagnetophoresis and magnetophoresis is the type of magnetic force experienced by the particles. Diamagnetophoresis is a process whereby the diamagnetic particles are manipulated in the magnetic carrier fluid of a higher magnetic susceptibility. It is necessary for a non-uniform magnetic field to be present in order for this process to be carried out. In this report, the author has created an analytical model to study the effect of diamagnetophoresis and the effect of different parameters on the behaviour of the diamagnetic particles. An analytical model present many advantages such as its capability of running large number of simulation, conducting of optimization simulation and also providing exact solution at each point in the solution space. The parameters which were investigated are the diamagnetic particle size, fluid flow rate and the magnetic field strength. It was concluded that high efficiency of particle sorting can be obtain through increasing particle size, decreasing flow rate and increasing magnetic field strength. The analytical model presented in this report has induce a possibility that the agglomeration of particles could occur in diamagnetophoresis process. Future work can be done on the study of agglomeration effect and the effect of the shape of microchannel on the diamagnetophoresis effect.